2017
DOI: 10.5993/ajhb.41.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Distress Tolerance Links Sleep Problems with Stress and Health in Homeless

Abstract: Many homeless individuals endure sleep problems. Given the connections between sleep and morbidity and mortality, results further support the need for more attention directed toward facilitating improvements in sleep quality to improve the quality of life of homeless adults, potentially including attention to improving distress tolerance skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Homelessness-both sheltered and unsheltered-is associated with poor sleep quality and insufficient duration (1)(2)(3). Insomnia, which refers to dissatisfaction with sleep quantity or quality (4), can both contribute to and be a consequence of disproportionately high rates of disease found among adults experiencing homelessness, including obesity, hypertension, cancer, and depression; it can also contribute to early mortality that is well documented in this population (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Homelessness-both sheltered and unsheltered-is associated with poor sleep quality and insufficient duration (1)(2)(3). Insomnia, which refers to dissatisfaction with sleep quantity or quality (4), can both contribute to and be a consequence of disproportionately high rates of disease found among adults experiencing homelessness, including obesity, hypertension, cancer, and depression; it can also contribute to early mortality that is well documented in this population (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Adults experiencing homelessness were recruited within two independent studies on health and health risk factors. Participants for Study 1 were recruited in the summer of 2013 in Dallas, TX [37], and participants for Study 2 were recruited between July and August of 2016 from 6 homeless-serving agencies in Oklahoma City, OK [38]. Participants from both studies were recruited using flyers placed around the shelter areas and targeted settings.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Inclusion criteria were: aged 18 or over, English-speaking, at least a 7th grade English literacy level as indicated by a score of >4 on the Rapid Estimate of Adult Literacy in Medicine-Short Form [39], and receiving services and/or shelter at the targeted agencies. Overall, 470 participants were screened in Study 1 and 648 were screened in Study 2, from which 76 (Study 1) and 38 (Study 2) individuals were ineligible for participation (for more information, see [37,40] and [38,41]). Overall, 394 (Study 1) and 610 (Study 2) participants enrolled.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Lower perceived distress tolerance has been associated with various psychological symptoms, including depression and PTSD [ 15 , 16 , 17 , 18 ]. In the limited available research, lower perceived distress tolerance has been identified as a link between sleep problems and stress [ 19 ]. Further, distress tolerance has shown significant indirect effects on the association between food insecurity and physical and mental health among adults who experience homelessness [ 20 ].…”
Section: Introductionmentioning
confidence: 99%